Event-study approach: The case of Airbnb and hotel stocks - Tchai Tavor; Sharon Teitler-Regev (Journal of Applied Economics, 2024)
This study investigates the impact of Airbnb announcements on hotel stock prices across ten countries, distinguishing between exact- and general-location announcements. We found that while general announcements have minimal impact, those with exact locations consistently reduce hotel stock prices, as evidenced by negative cumulative abnormal returns (CAR) trends. The primary impact occurs within the [-3, +1]-day window surrounding the announcement. These robust findings persist across various tests, underscoring their reliability. Implications include the importance of investor awareness regarding location-specific announcements and the need for regulatory examination of information disclosure practices on platforms like Airbnb., n.d. The study offers valuable insights for investors and policymakers navigating the dynamic landscape of the hospitality industry in the age of online platforms.
Keywords: 330; Airbnb; Event studies approach; hotel companies; market efficiency